The Influence Of Service Quality On Customer Satisfaction At Bank Mandiri Pelindo Place - Ricky Arif Candra; Liling Listyawati; Damajanti Sri Lestari (Cita konsultindo, 2025)
This study aims to analyze the impact of service quality on customer satisfaction at Bank Mandiri Pelindo Place Surabaya. In the context of the increasingly competitive banking sector, service quality becomes a key factor determining customer satisfaction. The methodology used in this research is quantitative with descriptive and associative designs, involving 96 respondents who are customers of Bank Mandiri Pelindo Place Surabaya. Data collection was conducted through questionnaires. The analysis results show a significant positive influence between service quality and customer satisfaction. The F-test results indicate that service quality simultaneously affects customer satisfaction, while the t-test shows a positive partial effect. Thus, the improvement in service quality at Bank Mandiri Pelindo Place Surabaya is likely to enhance customer satisfaction, thereby strengthening customer loyalty and the bank's reputation.